Letter from Lieutenant Commander J. D. Marvin to James Curtis Booth, February 18, 1872 - Marvin, J. D. (1872)
Lieutenant Commander J. D. Marvin follows up with James Curtis Booth (1810-1888) from his letter of February 2 about the use of silver or copper in ordinance experiments at DuPont’s Powder Mill. Marvin reports that Booth's solution for silver disk preparation worked.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; E.I. du Pont de Nemours & Company; Marvin, J. D.